Enhancing Water Resistance, Tensile Properties and UV-Shielding Capacity of Bovine Gelatin Films Modified with Epoxidized Soybean Oil and Glyoxal during Processing - González Granados, María Lucía (2020)
The present work is focused on the use of epoxidized soybean oil (ESO, 10 wt%) as hydrophobizing additive, glycerol as plasticizer (Gly, 30 wt.%),and glyoxal (GLX, 2 wt%) as low-toxicity cross-linking agent to endow bovine gelatin (BGe) films with improved moisture-related and UV-light barrier properties. Therefore, we aimed to investigate the effect of such modifications on the physicomechanical and structural properties of the ob-tained gelatin films. Modification was produced during intensive mixing and hot-press molding as a more environmentally sound and less time-con-suming processing method. ESO improved moderately the moisture content (MC) and water vapor permeability (WVP) of BGe film by 19% and 29%, respectively, but the total solubility of BGe-10ESO film evidenced the inability of ESO to induce covalent cross-linking. When GLX was add-ed to the BGe-10ESO formulation, several target film properties were upgraded; the film kept about 78% of its weight after 24 h of soaking in water, WVP improved by 56.8%, the tensile strength (TS) increased 48% while the stretching ability dropped in about 41%. The significant reduction in available free amino groups, from 100% (control) up to 21.9%, together with the increased color from light yellow to light orange confirmed that amino groups in BGe were involved in imine-based cross-linked structure when treated with glyoxal. Further, the high blocking ability of BGe-10ESO-2GLX film against UV-radiation may be useful in delaying UV-induced lipid oxidation when it is placed in contact with foods.